Evaluation of some introduced fresh market tomato (Solanum lycopersicum L) for genetic variability and adaptability in Ghana using morphological and molecular markers. - Gongolee, Godia Alpha Kortu (2014)
Thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture KNUST, Kumasi in partial fulfilment of the requirment for the award of M.Sc. (Plant Breeding), 2014